Perceived social support and health-related quality of life (HRQoL) in Tehranian adults: Tehran lipid and glucose study - Sara Jalali-Farahani; Parisa Amiri; Mehrdad Karimi; Golnaz Vahedi-Notash; Golshan Amirshekari; Fereidoun Azizi (Health and Quality of Life Outcomes, 2018)
Abstract Background Several studies have demonstrated the positive association between perceived social support and health-related quality of life (HRQoL) in certain groups; however, few studies have assessed this relationship in general population and between genders. This study aimed to investigate associations between socio-demographic factors, perceived social support and HRQoL among an urban Iranian population. Methods The study population were 1036 adults who had participated in Tehran Lipid and Glucose Study (TLGS). Data on socio-demographic information, perceived social support and HRQoL were collected using standard questionnaires by trained interviewers. Perceived social support and HRQoL were assessed using Iranian versions of the Multidimensional Scale of Perceived Social Support (MSPSS) and Short-Form 12-Item Health Survey version 2 (SF-12v2) respectively. Data on sets of associations among socio-demographic factors, perceived social support and quality of life were analyzed using Structural Equation Modeling (SEM) with IBM SPSS AMOS software. Results Mean ages were 50.3 ± 16.3 and 49.6 ± 14.0 years in men and women respectively and 40.9% of participants were male. In terms of perceived social support scores, except for family subscale scores (p = 0.003), there were no significant differences between men and women. However, men had significantly higher HRQoL scores, compared to women in all subscales. The findings of SEM analysis demonstrated that being married in both genders (p < 0.001) and lower age in men (p < 0.05) were significantly associated with higher level of perceived social support. In terms of physical HRQoL, being single and higher perceived social support in both genders and lower age and not having any chronic diseases, only in women were associated with higher physical HRQoL. However, for mental HRQoL, age and perceived social support had significant direct associations with mental HRQoL in both genders (p < 0.001); in women, being single (p < 0.05) and not having chronic diseases (p < 0.001) were also significantly associated with better mental HRQoL. Conclusion Perceived social support was found to be both directly and indirectly associated with physical and mental aspects of HRQoL in both genders. Current structural models provide beneficial information for planning health promotion programs aimed at improving HRQoL among Tehranian adults.